Intervención familiar como técnica terapéutica para disminuir el trastorno negativista desafiante en niños comprendidos entre 6 y 10 años de edad, en la Cdla. Barrio Lindo del Cantón Babahoyo – Los Ríos - Murillo Vera, Edwin Emilio (2020)
A case study is presented children with oppositional defiant disorder, a sample of 44 children / as those with disruptive and oppositional behavior in the family, school and in their interaction with other children / as with verbal and physical manifestations. We proceeded to perform the intervention of the minors who present said disorder with the collaboration of the parents applying the respective clinical observation allowing to detect the different types of signs that children with challenging negativist disorder present and clinical interview the same that allowed me to obtain information about of their relatives and therefore the patient, as an evaluation measures, a questionnaire of 10 questions, 8 of multiple choice and 2 of open questions was designed and used, addressed to parents to know what are the behaviors that children manifest and what actions parents take before them. A constant evaluation was carried out applying methods and techniques that allow information to be collected from both minors and parents. The intervention is based on systemic family therapy, said therapy was effective in reducing the characteristic symptoms of the challenging negativist disorder, applying techniques and strategies that allow restructuring the family system, self-control techniques, problem solving, training in techniques to regulate challenging behaviors. The results show an improvement in children's behavior, in family and social interaction, denoting greater control of their challenging behavior and reducing disruptive behavior.